ChemInform Abstract: Catalytic and Enantioselective α‐Functionalization of Oxindoles Through Oxidative Reactions with Naphthoquinones. Issue 1 (3rd January 2013) - Siau, Woon‐Yew; Li, Wenjun; Xue, Fei; Ren, Qiao; Wu, Minghu; Sun, Shaofa; Guo, Haibing; Jiang, Xuefeng; Wang, Jian
Abstract Optically active 3, 3‐disubstituted oxindoles are obtained by a new organocatalyzed aerobic oxidative method.